South African extension agent competencies and attitudes for the future: Results of a survey - Davis, Kristin E.; von Maltitz, Lindie; de Bruyn, Melanie; Van Niekerk, Johan; Ngomane, Tsakani (International Food Policy Research Institute, 2021)
Extension and advisory services are key to sustainable agriculture, resilient livelihoods, and inclusive growth. In South Africa, there is need for new training, skills, and attitudes by extension staff to meet the demands of the changing sector. The purpose was to find out South African extension agent competency levels, attitudes and mindsets, especially toward digital extension, to be relevant for the future. Using a population survey, we targeted all public and non-public extension staff from every province using an online and paper-based questionnaire. We examined existing competencies, new needs, and differences in attitudes and competencies by factors such as education, employer, age, and gender. We created an index of “digital readiness” and an index of “technological readiness” based on technology use and attitudes and compared by various factors such as sector, age, and gender. We find that while extension officers tend to have a good arsenal of technical skills, they are less equipped with functional skills. Several competencies and attitudes necessary for the new norms and standards for extension officers are lacking in a good proportion of respondents, such as inclusivity and empowerment. While extension staff recognize the importance of digital literacy for the future, only about half have received any training on the use of digital tools. We recommend that extension role players take a systems view to revitalize extension. For extension to perform effectively, we must go beyond skills and training. Extension departments and organizations also need a certain level of competencies, and the enabling environment should be conducive. We recommend that, in addition to rounding out the technical and functional expertise of South African extension and advisory services staff that adequate incentives and rewards are in place to ensure professionalism and motivation.